A Multidisciplinary Approach Combining Life Sciences, Chemistry, Environmental Sciences, and Environmental Engineering to Address Climate Change Challenges and Protect Ecosystems - Hamid, Sabreen Malek Alwan; Mahdi, Zahraa Ali Muhisin; Hizam, Badr Qasim Atshan; Mahdi, Hussein Kamel Kazem (American Journal of Biodiversity, 2025)
The complexity and scale of climate change in the 21st century demand solutions that integrate the scientific foundations of life sciences, chemistry, environmental sciences, and engineering with all levels of climate-change analysis and management. Action based solely upon a single field of study is unlikely to reduce climate-change risks and maintain Earth’s ecosystems over the long-term. Cutting-edge climate-change research requires a broad conception of integrative methods that bring all four scientific disciplines together to produce multidimensional mitigation and ecosystem-protection strategies. The varieties of problems addressed today often require extensive integration and interchange among the disciplines, as well as across broad spatial and temporal scales.